Enhancing the Entrepreneurial Capabilities of PKK Mothers through Training on a Variety of Healthy Snack Foods - Reswita, Reswita; Reflis, Reflis; Badrudin, Redy (Altifani Journal: International Journal of Community Engagement, 2022)
Along with the increasingly diverse demand in the field of daily food needs, especially for food, the snack food business is a business opportunity for PKK mothers to support their household economy. To increase knowledge and skills in running a food snack business, PKK mothers need entrepreneurship training in various healthy food snacks. This causes some PKK mothers to be constrained by limited knowledge in making various contemporary snack foods that are following market demand, have not been able to calculate capital or the cost of goods, and do not understand how to sell online. The purpose of this community service activity is to provide training on making various healthy snack foods for PKK mothers, calculating the cost of goods produced, and providing training on promotional and marketing techniques online. The results of this activity are: 1) The knowledge and skills of the trainees' mothers in making various healthy snacks increased, 2) The trainee mothers were able to calculate the cost of goods produced and set the selling price of products, increased knowledge and skills in online-based marketing, were able to cultivate the entrepreneurial spirit of PKK mothers, the household food consumption of PKK mothers of the training participants was increasingly diverse,  and the mothers of the trainees as a whole were satisfied with this service activity.